The Opium Economy and its Dual Role in Afghanistan: An Analysis of Livelihoods, Informal Growth, and Development (2004–2024) - Mohammad Bashir Bahrangi; Akhlaqi , Liaqat Ali (Science Tech Group, 2026)
This research examines the multifaceted role of illicit opium production in Afghanistan's economy from 2004 to 2024, with a focus on its contribution to rural livelihoods, informal economic activity, and long-term development constraints. Through a descriptive-analytical methodology utilizing secondary data from UNODC, the World Bank, and national sources, the study assesses the socio-economic impacts of drug production across three dimensions: household income, GDP contribution via the informal economy, and institutional development. Findings indicate that opium cultivation provided a critical income safety net for rural households, generating 3–5 times higher returns than legal crops and sustaining informal credit systems. Simultaneously, the opium economy constituted 10–15% of national GDP in peak years, functioning as a parallel financial system that facilitated foreign currency inflows but distorted formal markets and discouraged legal investment. However, this short-term economic functionality came at the cost of entrenched corruption, weakened governance, and hindered economic diversification, reinforcing a cycle of dependency and instability. This research directly addresses multiple Sustainable Development Goals (SDGs), particularly SDG 1.1 (eradicating extreme poverty) by demonstrating opium's role as a rural income safety net; SDG 8.3 (promoting development-oriented policies) by examining informal economic activities; and SDG 16.4 (reducing illicit financial flows) by analyzing how opium revenues fuel shadow economies and undermine institutions. The study concludes that transitioning away from opium reliance requires an integrated policy approach combining agricultural alternatives, rural finance, governance reform, and regional cooperation.